Model Magang Pendidikan Informal - Mira Nurlela; Adang Danial; Lulu Yuliani (Lifelong Education Journal, 2022)
The apprenticeship model is a training program given to learning residents by tutors or learning resources who are experienced in the field of crafts and production by applying it in informal education where this learning is carried out in a community environment where industry owners apply learning with the principle of kinship and participate in provide direction in the learning process. The purpose of this study was to find out how the informal education apprenticeship model process for wood craftsmen in the wood craft industry in Sukahurip Village, Tamansari District, Tasikmalaya City. This research was conducted because it was found that there was a wood craft home industry that implemented an informal education trainning model for wood craftsmen without any intervention and support from the local government. This study uses descriptive qualitative research methods. Data was collected by three methods, namely observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation and conclusion drawing. The results of this study indicate that the Informal Education Apprenticeship Model based on analysis of research in the field is carried out by the owner of the craft industry to craftsmen or apprentices covering ten public education standards. The internship is carried out by the owner, which begins with the recruitment of learning residents who come from the surrounding environment and from outside. The training process in learning is carried out in several stages, namely the stage of pattern making, wood cutting, wood lathe, wood sanding and wood roasting. After the learning process, the citizens learn to have the knowledge, skills and abilities in making handicrafts and some even switch professions to become independent apprentices. The conclusion of this study is that the informal education trainning model is carried out by the owner of the craft industry on the principle of kinship where in the learning process the learning residents are guided directly by the owner himself and in terms of the relatively low cost so that it does not burden the learning community, then the learning community can gain knowledge, skills and even abilities. in the manufacture of handicrafts and the movement of professions that were previously apprentices in the industry to become independent apprentices.